Tax Restitution for Acquisition of Land and Building Rights (Bphtb) for Default by the Buyer Resulting in the Cancellation of the Sale and Purchase Deed - Al Farra, Kamal (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to analyze the implementation of Land and Building Acquisition Tax (BPHTB) restitution in the event of a default by the buyer resulting in the cancellation of the Sale and Purchase Deed (AJB). This study uses a sociological juridical method, namely by examining the application of applicable legal provisions in practice through interviews, observations, and studies of real cases in the field. Data were obtained from interviews with relevant agency officials and the community who experienced the BPHTB restitution process, then analyzed qualitatively to obtain an empirical picture of the implementation of the policy. The results of the study indicate that normatively, BPHTB restitution applications can be made based on the provisions of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments (HKPD Law) and Regulation of the Minister of Finance Number 51/PMK.07/2016 concerning Settlement of Refunds for Excess Payments of Land and Building Acquisition Tax and Settlement of Applications for Rural and Urban Land and Building Tax Services. In the context of a land sale or purchase that is cancelled due to default, land rights never transfer, so the BPHTB paid should be returned to the taxpayer. However, in practice, the restitution process often encounters administrative and legal obstacles, particularly regarding the cancellation of the AJB, which requires a court decision or a notarial deed of cancellation.